2011
DOI: 10.1038/ejhg.2011.240
|View full text |Cite
|
Sign up to set email alerts
|

Codon 72 polymorphism (rs1042522) of TP53 is associated with changes in diastolic blood pressure over time

Abstract: p53 is involved in stress response, metabolism and cardiovascular functioning. The C-allele of rs1042522 in the gene encoding for p53 is associated with longevity and cancer. In this study, we aimed to investigate the association of rs1042522 with changes in blood pressure, BMI and waist circumference using a longitudinal approach. Rs1042522 was analyzed in two longitudinal studies; the Doetinchem Cohort Study (DCS) and the Botnia Prospective Study (BPS). Changes in quantitative traits over time were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
1
28
2
Order By: Relevance
“…In keeping with the latter, Burgdorf and coworkers’ metaanalysis of diabetes did find the R72 allele to increase risk of Type 2 diabetes by 6% [39], though there are no data for diabetic nephropathy per se . A relationship with BP, has also been reported [40], but we do not confirm this. There are large differences in frequency between continental populations, with the ancestral P72 allele common in Africa, and the R72 allele common in European and Asian populations (Table 5).…”
Section: Discussioncontrasting
confidence: 89%
“…In keeping with the latter, Burgdorf and coworkers’ metaanalysis of diabetes did find the R72 allele to increase risk of Type 2 diabetes by 6% [39], though there are no data for diabetic nephropathy per se . A relationship with BP, has also been reported [40], but we do not confirm this. There are large differences in frequency between continental populations, with the ancestral P72 allele common in Africa, and the R72 allele common in European and Asian populations (Table 5).…”
Section: Discussioncontrasting
confidence: 89%
“…These data suggest that the R72 variant may predispose individuals to obesity, which subsequently leads to increased susceptibility to type 2 diabetes. In support of this hypothesis, a recent cohort study of over 2,500 Dutch and Finnish subjects found a significant association between R72 and increased waist circumference (Reiling et al, 2012). Similarly, a separate study showed that the association between BMI (body mass index) and diabetes is much stronger in homozygous R72 individuals (Gloria-Bottini et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…A cohort study of over 2,500 Dutch and Finnish subjects found that the R72 variant is associated with increased waist circumference (Reiling, et al 2012). These data suggested that the R72 variant might predispose individuals to adiposity/obesity, and that this might then lead to increased risk for the development of type 2 diabetes.…”
Section: Polymorphisms In the P53 Pathway: The Codon 72 Polymorphism mentioning
confidence: 99%